PERILAKU EARNINGS MANAGEMENT DI SEKITAR PERUBAHAN TARIF PAJAK TAHUN 2008 - Suyanto Suyanto (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2013)
This study aims to test the level of earning management before and after the income tax rate reduction for 2008 fiscal year. The samples were 21 banking companies listed in Indonesia Stock Exchange, which has provides loans to SMEs. The analysis using paired samplest-test to test these differences of earning management before and after the income tax rates changes. The results showed that earning management in the high tax rate was higher than in the lower tax rate. This shows that management has responded the income tax rates changes to take the opportunity. Keywords: discretionary accruals, earnings management, corporate income tax changes.